Doxazosin Effects on Cholinergic and Adrenergic Responses in Rat Isolated Detrusor Smooth Muscle Preparations From Obstructed Bladder - Coşkun Usta; Erdal Kukul; Mehmet Yalçınkaya (Elsevier, 2004)
We investigated the effect of doxazosin on cholinergic and adrenergic agonists responses in detrusor smooth muscle preparations from sham-operated and 2-week partially obstructed rat bladders. Male Wistar albino rats, 200 - 250 g, were randomly allocated to 4 experimental groups consisting of 12 animals each: sham-operated bladder, sham-operated bladder treated with doxazosin, partially obstructed bladder, and partially obstructed bladder treated with doxazosin. Partial outlet obstruction of the rat was surgically induced. The response to carbachol (10−7 - 10−4), isoproterenol (10−6 - 10−3 M) and 80 mM KCl were recorded. Carbachol caused concentration-dependent contractile responses in the detrusor smooth muscles from sham-operated and partially obstructed bladder. Isoproterenol produced concentration-dependent relaxation responses in the detrusor strips from all groups. Dose-response curves for carbachol and isoproterenol showed a shift to the left in rat detrusor smooth muscles from partially obstructed bladder when compared with the results obtained in detrusor muscles from sham-operated bladder. These responses were reversed to normal by doxazosin treatment in rat detrusor smooth muscles from partially obstructed bladder. KCl produced contractile responses in rat detrusor smooth muscles from all groups. The contractile responses to KCl were not significantly changed in all groups. We have shown that carbachol and isoproterenol responses were shifted to the left in rat detrusor smooth muscles from partially obstructed bladder and these responses were reversed by doxazosin treatment.